2013
DOI: 10.1002/nml.21078
|View full text |Cite
|
Sign up to set email alerts
|

Leadership Style in Relation to Organizational Change and Organizational Creativity: Perceptions from Nonprofit Organizational Members

Abstract: As the environment within which organizations act continues to change and becomes increasingly competitive, maintaining an organizational climate that supports change and encourages creativity is a key objective for organizational leaders. This article examines the relationship between leadership style (transformational, transactional, laissez-faire) and members' perceptions of the psychological climate for organizational change readiness and psychological climate for organizational creativity. Results indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 77 publications
0
40
0
Order By: Relevance
“…As the interaction between leaders and followers is essential for successful change phase (Kotter, 1995), however, in laissez-faire leadership, there exists minimum interaction between leaders and followers (Northouse, 2007). Therefore, laissez-faire leadership negatively affects the change process, particularly in non-profit organizations (Lutz Allen et al, 2013). Hence, individuals with laissezfaire leadership behavior will negatively affect OCC.…”
Section: Discussionmentioning
confidence: 99%
“…As the interaction between leaders and followers is essential for successful change phase (Kotter, 1995), however, in laissez-faire leadership, there exists minimum interaction between leaders and followers (Northouse, 2007). Therefore, laissez-faire leadership negatively affects the change process, particularly in non-profit organizations (Lutz Allen et al, 2013). Hence, individuals with laissezfaire leadership behavior will negatively affect OCC.…”
Section: Discussionmentioning
confidence: 99%
“…First, the results of our study extend our understanding of the effects of TL. The previous research mostly examines TL in the organizational context and focuses on the organizational outcomes such as organizational change (for example, Lutz Allen, Smith, and DaSilva ). However, the TL research in higher education, specifically within the context of collectivist cultures, is limited.…”
Section: Discussionmentioning
confidence: 99%
“…As such, innovation in the human service organization can be of greater importance and value than in other social organizations (Drucker, 1995;Mano, 2010). Because of this importance of organizational innovation for nonprofit human service organizations, studies have investigated and reported determinants of innovation including organizational culture (Crossan & Apaydin, 2010;Jaskyte & Dressler, 2005), leadership (Jaskyte, 2004;Lutz Allen, Smith, & Da Silva, 2013;Shin & McClomb, 1998), internal organizational properties-such as centralization and formalization (Jaskyte, 2011;Shin & McClomb, 1998)external environmental pressures or turbulence (Gummer, 1989), and organizations' general characteristics such as size (Jaskyte, 2013;Jaskyte & Dressler, 2005) and the age of the organization (Shin & McClomb, 1998).…”
Section: Introductionmentioning
confidence: 99%